13th December 3rd Sunday of Advent - Plant, Stephen (2015)
The article presents the author's reflection on the gosphel sermon for the 3rd Sunday of Christmas season which focuses on God's intervention for people in need. The author cites the victims of earthquake disaster in Nepal on April 25, 2015, on their divine intervention and faith with God. He also emphasizes on the value of plain repentance in transfoming lives of people.
Keywords: Advent; EARTHQUAKE damage; INTERVENTION (Social services); People with disabilities; Personality Change; Religious Aspects